Assessment of entrepreneurial inclination among the seaweed operator at Semporna, Sabah Using EAO Model / Nurul Hisifbli Ibrahim, Abdul Rahman Saili - Ibrahim, Nurul Hisifbli; Saili, Abdul Rahman (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
Seaweed cultivation is an export-oriented aquaculture subsector that is rapidly spreading specifically in South East Asia. Recently, almost all segments of seaweed industry are still facing many obstacles, especially at the level of small-scale farmers’ management in the production and processing industry. The most obvious issue is linked to the development of seaweed operators. The main objective of this study is to assess the seaweed operators’ attitude towards the entrepreneurial inclination. The survey was conducted among the seaweed operators in Semporna based on entrepreneurial attitude orientation (EAO) questionnaire. The result shows that the adjusted R square (Adj. R2) value is equivalent to 0.301. This indicates that 30.1 per cent of the entrepreneurial intention were explained by the four entrepreneurial attitude subscales; achievement, innovation, personal control and self-esteem. The result exhibits that the achievement, innovation and personal control were statistically significant at 95 per cent confidence interval. Self-esteem shows no significant relationship and thus signifies subscale as did not contribute much to the regression. The EAO factors contributes little to the regression of the entrepreneurial inclination, which indicates that the other factor such as socioeconomic inputs such as skills, knowledge, extension agent, gender and financial roles might include in the future study.